Master Teachers’ Competence, Technical Assistance and Challenges in Educational Research: Basis for Training Enhancement - Am-is, Euann M. (International Journal of Research in Interdisciplinary Studies, 2025)
Master Teachers as pivotal instructional leaders are expected to model best practices not only in teaching but also in advancing a research-oriented culture that supports evidence-based instruction and continuous school improvement. This study aimed to assess the research competence of Master Teachers and examine the extent of technical assistance they provide to educators in conducting research within the context of the Philippine basic education system. The study employed descriptive-quantitative research using a researcher’s made survey questionnaire to determine the research competence of 16 master teacher-respondents and examine the extent of technical assistance in terms of Idea Sharing, Professional Development and Enhancement of Learning Environment. The challenges encountered by the respondents in conducting research were also explored. These data were analyzed and collated using suitable statistical tools and were interpreted and discussed consequently. The findings of the study showed that the master teachers are competent in various domains of educational research, particularly in data collection and research question framing. The study revealed that Master Teachers demonstrated a moderate level of support in terms of technical assistance, especially in enhancing the learning environment, sharing ideas, and promoting professional development. The study also showed that Master Teachers face significant challenges in conducting educational research, largely due to excessive workload, limited training opportunities, and lack of time. Furthermore, the study revealed that there is a significant relationship between master teachers’ competence and the technical assistance provided. Meanwhile, their profile such as age, educational attainment and the number of research trainings attended showed no significant influence in their extent of technical assistance on research.